2022
DOI: 10.1002/jmv.28273
|View full text |Cite
|
Sign up to set email alerts
|

IgG autoantibodies against ACE2 in SARS‐CoV‐2 infected patients

Abstract: How frequently autoantibodies against angiotensin‐converting enzyme 2 (ACE2) occur in patients infected by SARS‐CoV‐2 is understudied and limited to investigations on a small sample size. The presence of these antibodies may contribute to the long‐lasting effects of COVID‐19 observed in some individuals, particularly if IgG‐class antibodies would emerge in patients. This study assessed the prevalence of IgG autoantibodies against ACE2 in 1139 patients infected with SARS‐CoV‐2 and examined their relationship wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Autoantibodies were detected during the acute phase of COVID-19 [316] , [317] , [318] , [319] , [320] , [321] , [322] , [323] , [324] , [325] , [326] , [327] , [328] , [329] , [330] , [331] , [332] , [333] , months afterwards (predicting PACS symptoms) [334] , [335] , in PACS [336] , [337] , [338] , [339] , [340] , and in PCVS [295] , [298] , [341] , [342] , [343] , [344] , [345] , [346] , [347] , [348] , [349] , [350] , [351] , [352] , [353] , [354] , [355] , [356] , [357] , [358] , [359] , [360] , [361] , [362] , [363] , [364] , [365] . In the absence of PCVS after COVID-19 vaccination, autoantibodies are generally not present [366] , [367] , [368] .…”
Section: Sars-cov-2 Infection- and Covid-19 Vaccination-induced Syndr...mentioning
confidence: 99%
“…Autoantibodies were detected during the acute phase of COVID-19 [316] , [317] , [318] , [319] , [320] , [321] , [322] , [323] , [324] , [325] , [326] , [327] , [328] , [329] , [330] , [331] , [332] , [333] , months afterwards (predicting PACS symptoms) [334] , [335] , in PACS [336] , [337] , [338] , [339] , [340] , and in PCVS [295] , [298] , [341] , [342] , [343] , [344] , [345] , [346] , [347] , [348] , [349] , [350] , [351] , [352] , [353] , [354] , [355] , [356] , [357] , [358] , [359] , [360] , [361] , [362] , [363] , [364] , [365] . In the absence of PCVS after COVID-19 vaccination, autoantibodies are generally not present [366] , [367] , [368] .…”
Section: Sars-cov-2 Infection- and Covid-19 Vaccination-induced Syndr...mentioning
confidence: 99%
“…There are also reports on the autoantibodies against ACE2 that serves as the receptor for cellular entry of SARS‐CoV‐2 59,74,75 . At the same time, ACE2 plays a role in the renin−angiotensin hormone system by transforming angiotensin II into protective angiotensin (1−7) and regulating blood volume, hemato‐ and erythropoiesis, apart from its functions in immunity and stem cell maintenance 76 .…”
Section: Autoantibodies Against Components Of the Cardiovascular Systemmentioning
confidence: 99%
“…58,78 However, one study reported the seroprevalence of IgG anti-ACE2 antibodies in 1.5% of subjects, mostly men and patients who underwent mild COVID-19 (although they were sporadically also found in severe and asymptomatic cases). 59 It can be suggested that such antibodies may be produced as a part of immune mechanisms leading to the suppression of the viral spread or represent so-called homebodies that recognize the binding partner of the original viral protein. 59,79 Although anti-ACE2 antibodies can be detrimental to cardiovascular function as well as a variety of organs causing tissue inflammation, 80,81 it should be noted that their expected seroprevalence, unrelated to COVID-19, is not known, particularly in the case of IgG antibodies.…”
Section: Autoantibodies Against Components Of the Cardiovascular Systemmentioning
confidence: 99%
See 2 more Smart Citations